Development of social contact and loneliness measures with validation in social prescribing. Issue 2 (14th May 2021) - Benson, Tim; Seers, Helen; Webb, Nicola; McMahon, Philippa
Abstract : Aims: This paper describes two patient-reported measures of social contact and loneliness, which are closely related concepts. The first measure (R-Outcomes Social Contact measure) was developed from scratch, based on customer needs and literature review. It covers emotional and social aspects using positive terms. The second measure (R-Outcomes Loneliness measure) is adapted from the GSS Loneliness Harmonised Standard. Both measures are patient-reported outcome measures, based on patients' own perception of how they feel. Method: This development started in 2016 in response to customers' requests to measure social contact/loneliness for patients in social prescribing projects. Both measures are compared with three other loneliness measures (the GSS Loneliness Harmonised Standard, De Jong Gierveld and Campaign to End Loneliness). Both measures are short (36 and 21 words, respectively). Mean improvement is reported as a positive number on a 0–100 scale (where high is good). We tested the psychometric performance and construct validity of the R-Outcomes Social Contact measure using secondary analysis of anonymised data collected before and after social prescribing interventions in one part of Southern England. Results: In the validation study, 728 responses, collected during 2019–2020, were analysed. 90% were over 70 years old and 62% women. Cronbach's α=0.76, which suggests that it is appropriate to use a single summary score. Mean Social Contact scores before and after social prescribing intervention were 59.9 (before) and 66.7 (after, p<0.001). Exploratory factor analysis shows that measures for social contact, health status, health confidence, patient experience, personal well-being, medication adherence and social determinants of health are correlated but distinct factors. Construct validation shows that the results are consistent with nine hypotheses, based on the loneliness literature. Conclusion: The R-Outcomes Social Contact measure has good psychometric and construct validation results in a population referred to social prescribing. It is complementary to other R-Outcomes measures.